Physicochemical and functional properties of wheat (Triticum aestivum) and selected local flours in the Philippines - Alviola, Juma Novie A.; Monterde, Viena G. (2018)
Exploring locally available wheat alternatives will be advantageous to the domestic flour and baking industry and to the Filipino farmers. This will also offer value-added products to the growing gluten-free market. The physicochemical and functional properties of different flours (non-glutinous and glutinous rice, sweet potato, mung bean, banana, and sago) were determined and compared with all-purpose wheat flour. The bread quality parameters of these flours were correlated with flour properties. The commercially available flours (wheat, rice, sweet potato) were significantly whiter than the mung bean, banana, and sago flours. In terms of proximate composition, mung bean flour had the highest protein (22.57%), fiber (2.19%), and ash (4.72%) contents among the flours. Sweet potato flour, on the other hand, had the highest total carbohydrates (85.22%), starch (81.50%), and amylose (26.30%) contents. It was the most viscous but was unstable upon heating (i.e., highest peak and breakdown viscosities). Banana flour had the highest water absorption capacity and the second highest swelling power at 85°C next to sago flour. The absence of gluten in the non-wheat flours led to firmer and denser bread. Bread from inherently pigmented flours had a significantly darker crumb, but only mung bean flour produced a significantly darker crust than the control (100% wheat). Correlation analysis revealed that using flours with relatively lower fiber and amylose contents, smaller particle size, and lower breakdown viscosity ? but higher water absorption capacity ? lowers the chances of producing firm and dense bread.